Self-injurious behavior and foreign body entrapment in the root canal of a mandibular lateral incisor - B N Rangeeth; J Moses; N Venugopal Reddy (Wolters Kluwer Medknow Publications, 2011)
Self-injurious behavior is a deliberate alteration or damage without suicidal indent. Herein, we report a patient who had caused intentionally self-trauma to his left lower permanent canine and placed a long metallic foreign body into the root canal. History revealed a habit of placing metallic objects in the form of stapler pins into the mouth, but closer examination revealed the habit to be more as a method of self-injurious behavior. Following an episode of severe pain, the tooth was endodontically treated after removal of the foreign body that was corroding. Clinical significance of the case report is that the patient may just be put off as having a habit of inserting foreign objects into the mouth, but the behavior was more self-injurious in nature.